Mengenal Mushaf Al-Qur'an Standar Usmani Indonesia: - Zainal Arifin (SUHUF, 2011)
Indonesia has used a Qur’anic standard text as a reference for publishing the Qur’an since 1984. There are three kinds of standard texts in Indonesia: the Othmani Qur’anic standard text, the Bahriyah Qur’anic standard text, and the Braille Qur’anic standard text of Indonesia. This article seeks to renew readers’ acquaintance with the standard text following its two editions in 1983 and 2002. The Qur’anic standard text of Indonesia is based on Hafs from ‘Asim. Some distinct aspects of the text can be observed in the signs of reading, the completion of the rule for reading of the holy Qur’an (tajwid), and symbols such as sifir, isymām, imālah, tashīl, as well as other elements.